The Phylogeny of Bornean Swamp Buffalo (Bubalus bubalis) Analysis Based on D-loop Mitochondrial DNA Sequence Variation - Suhardi; A. Wibowo; W. P. B. Putra; P. Summpunn (Tropical Animal Science Journal, 2023)
Swamp buffalo (Bubalus bubalis) is one of the Indonesian germplasm that adapts well to Borneo Island. This study aimed to determine the genetic diversity, phylogenetic tree, and phylogeographic structure of Bornean swamp buffalo based on control region (D-loop) mitochondrial DNA sequences. A total of 120 animals were collected from three populations in Indonesia, i.e., the North, East, and South of Kalimantan Provinces. Along 1140 bp of D-loop mtDNA gene of Bornean swamp buffaloes was amplified with a design primer of F: 5'-CAA CAC CCA AAG CTG AAG TT-3’ and R: 5'-CGC TCC TCT TAG TCT CGT TG-3’. Therefore, the forward and reverse sequencing was performed to visualize the full length of D-loop mtDNA gene sequence (1140 bp). Results showed that a total of 47 haplotypes were detected in the animal study, with haplotype and nucleotide diversities of 0.936 and 0.005, respectively. Consequently, two haplogroups were observed in the animal study, i.e., Haplogroup A (North) and Haplogroup B (East and South). Based on structure analysis, Bornean swamp buffaloes were comparable to filing swamp buffaloes of China based on structure. According to the analysis of molecular (AMOVA), the geographical component contributed over 56.44% of the total mtDNA sequence variations. In conclusion, it was discovered that the haplogroups of buffalo from the East and South populations were identical.